Effect of Agaricus blazei Murill on exploratory behavior of mice-model - Ali,M. M. (2024)
Abstract Increased anxiety and depressive symptoms have reported to be its association with long term illness. Because of having unwanted effects of newly available drugs, patients administering anxiolytic drugs usually discontinue the treatment before they are completely recovered. Therefore, there is a serious need to develop new anxiolytic drugs. The anxiolytic effect of hydro-alcoholic extract of Agaricus blazei in animal models was assessed. 24 male mice (Mus musculus genus) were included in the study. Four groups were prepared and each group contained six animals. The groups were vehicle control, positive control (diazepam 1.0 mg/kg, i.p.) as well as two treatment groups receiving Agaricus blazei hydro-alcoholic extract at a dose of 136.50 mg/kg and 273.0 mg/kg orally. The Marble burying test, Nestlet shredding test and Light and Dark box test used to assess anxiolytic activity. Mice administered with diazepam 1.0 mg/kg, i.p. while hydro-alcoholic extract of AbM (136.50 and 273.0 mg/kg, respectively) was administered via oral route which exhibited marked reduction in number of marbles-burying as compared to vehicle control group. Mice administered with diazepam 1.0 mg/kg, i.p. and Oral administration of hydro-alcoholic extract of AbM (136.50 and 273.0 mg/kg, respectively) exhibited significant decrease in nestlet shredding in comparison to vehicle control group. The oral administration of hydro-alcoholic extract at a dose of 136.5mg/kg and 273mg/kg showed elevation in time spent in light box and was comparable to standard treated group while time spent by mice following oral administration of hydro-alcoholic extract of Agaricus blazei at a dose of 273.0 mg/kg also showed elevation and was found to be more near to standard treated group (diazepam 1 mg/kg, i.p.).